Hubungan Kasta Dengan Status Sosial Masyarakat Adat Bali - Putri Galuh Pitaloka; Thalia Salma Putri Kamilah; Nugroho Dewo Dharmawan; Akmal Zaki; Atik Winanti (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This article explores the caste system in Bali which has become an integral part of the social and cultural structure of Balinese society. The relationship between caste and social status reflects a deep and distinctive aspect of the structure of Balinese society. This article contains the history and how caste affects daily life and interaction patterns in Bali. In conclusion, the article also discusses the responsibilities of caste system holders in Bali involving a series of roles that are important in maintaining social and cultural balance in the Balinese indigenous community. They are responsible for maintaining and preserving the traditions and cultural values associated with each caste. In this article we can find out about the relationship and social system of caste in Bali.